Experimental Research on the Influence of Particle Size on Sand Production during Gas Hydrate Dissociation via Depressurization - Xu, Ya-Ting; Wang, Yi; Li, Xiao-Sen; Li, Xiao-Yan; Li, Gang; Deng, Fu-Cheng (AMER CHEMICAL SOC, 2022)
Natural gas hydrates are considered as a potential energy resource. However, the characteristics of hydrate-bearing sediments lead to production difficulty. Field tests of gas production from hydrate reservoirs are frequently interrupted on the basis of sand production. The particle size of the reservoir could affect the mechanical model of gravel migration during hydrate dissociation. The reservoir particle size has a certain impact on the strength of hydrate reservoirs. In this study, sand production behaviors in methane hydrate reservoirs with different particle size quartz sands were investigated by a novel experimental apparatus, and the experiments on hydrate dissociation via depressurization were conducted to investigate the relationship between the particle size and reservoir damage. The experimental results indicate that there is a certain particle size beneficial for particle migration. The larger particle size leads to a small area of active sand, and the smaller particle size leads to a small amount of particle migration. In this work, the reservoir with a median particle size of 118.417 mu m experienced the largest amount of sand production. Meanwhile, the particle migration behaviors in the hydrate reservoirs with different particle sizes are analyzed. To avoid sand production, for large-particle porous media reservoirs, the position of the opening of the wellbore should be in the upper layer of the reservoir, whereas for small-particle porous media reservoirs, the position of the opening of the wellbore should be in the bottom layer of the reservoir.